2023
DOI: 10.1002/smtd.202300338
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Sources of Bio‐Inspiration and Materials for Robotics and Actuators

Abstract: Bionic robotics and actuators have made dramatic advancements in structural design, material preparation, and application owing to the richness of nature and innovative material design. Appropriate and ingenious sources of bio‐inspiration can stimulate a large number of different bionic systems. After millennia of survival and evolutionary exploration, the mere existence of life confirms that nature is constantly moving in an evolutionary direction of optimization and improvement. To this end, bio‐inspired rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 179 publications
(269 reference statements)
0
1
0
Order By: Relevance
“…Many creatures in nature are constantly adaptively evolving in order to adapt to environmental changes [ 13 , 14 ]. With the in-depth study of bionics, human beings have found a variety of biological structures [ 15 , 16 ] in nature that are efficient and conform to the laws of thermodynamics and hydrodynamics. These structures provide a lot of inspiration for human design.…”
Section: Introductionmentioning
confidence: 99%
“…Many creatures in nature are constantly adaptively evolving in order to adapt to environmental changes [ 13 , 14 ]. With the in-depth study of bionics, human beings have found a variety of biological structures [ 15 , 16 ] in nature that are efficient and conform to the laws of thermodynamics and hydrodynamics. These structures provide a lot of inspiration for human design.…”
Section: Introductionmentioning
confidence: 99%